Features of Use of the Technology «Jena Plan» by Peter Petersen in Secondary Schools - Lyudmyla Mashkina (Pedagogical Discourse, 2016)
In the article the peculiarities of using technology «Jena Plan» P.Petersena in secondary schools have been revealed. The basic ways of communality education as a condition of the individual in the collective life have been studied. The essence of the functioning of basic groups and institutions «baptized» have been shown. It is indicated that each must personally interact with the material and the spiritual world for the development of individual, social and cultural environment, has the right to be an innovator in the field of culture. People need to work towards a society in which respect the value and dignity of each individual, which promotes the development of each individual and encourages him or her where the contradictions between individuals or groups of people settled fairly and constructively and in which the Earth and the cosmos are treated with respect and care. School is an organization which should be relatively self-government and human interaction related to the educational process. The content of the curriculum determined by the needs, interests and children the basics of culture in the society, which are considered essential for personal development. Teaching is done by creating learning situations. The processes of teaching and learning consists of rhythmic repetition of key activities. They are dialogue, play, work, holiday. The school should alternate developing education, free play and independent study of educational material. The training is an essential element of group work, where the behavior and success of the child is judged in terms of this particular child. It deals with the form of the educational process, including individual and group, dialogic, games, sports and others. The areas of cooperation of professional teachers and parents, involved in the educational process, carry moral and material support to the school. The attention is focused on the basic principles of Jena Plan School.Key worlds: Peter Petersen, educational technology «Jena Plan», secondary schools, communality, pedagogic principles of Jena Plan, schools, base band, Institute «baptized», rhythmic, weekly plan.